The Effects of Same- and Other-Race Facial Expressions of Pain on Temporal Perception - Huang, Shunhang; Qiu, Junjie; Liu, Peiduo; Li, Qingqing; Huang, Xiting (Frontiers in Psychology, 2018)
Previous studies suggested that threatening stimuli lengthen subjective duration, while facial expressions of pain were found to produce a shortening effect on temporal perception in a recent study. Moreover, individuals’ responses to others’ pain were influenced by the racial group relationship. However, the effects of same- and other-race pain expressions on temporal perception remain unknown. The aim of the present study was to identify the effect of expressions of pain on temporal perception and to explore whether this effect is modulated by racial group relationship. In a temporal bisection task, Chinese participants were presented with pain or neutral expressions displayed by Caucasian (other-race) or Asian (same-race) models in a 400 1600 ms or 200 800 ms condition. Expressions of pain were rated as more arousing, negative and dislikable than neutral expressions, and these scores were not significantly different between same- and other-race faces. The results of the temporal bisection task revealed that both same- and other-race pain expressions lengthened perceived duration in the 400 1600 ms condition, but only same-race pain expressions produced this effect in the 200 800 ms condition. We argue for the existence of a short-lived lengthening effect of pain expressions on temporal perception caused by arousal and attention, which happens earlier for same-race pain expressions than for other-race pain expressions.